Temperature variability increases the onset risk of ischemic stroke: A 10-year study in Tianjin, China - Chen, Zhuangzhuang; Liu, Peilin; Xia, Xiaoshuang; Wang, Lin; Li, Xin (Frontiers in Neurology, 2023)
Background: Epidemiological evidence suggests a correlation between ambient temperature and ischemic stroke. However, evidence on the impact of daily temperature variability on the onset of ischemic stroke is lacking and limited. Objective: We aimed to investigate the short-term association between temperature variability and ischemic stroke occurrence in Tianjin. Methods: We performed a 10-year analysis of ischemic stroke patients hospitalized in two affiliated hospitals of Tianjin Medical University from 2011 to 2020. Daily meteorological data were collected from the Tianjin Meteorological Bureau. Temperature variability was calculated from the standard deviation (SD) of daily minimum and maximum temperatures over exposure days. A quasi-Poisson generalized linear regression combined with distributed lag non-linear model was used to estimate the effect of temperature variability on daily stroke onset, while controlling for daily mean temperature, relative humidity, long-term trend and seasonality, public holiday, and day of the week. Results: Temperature variability was positively associated with ischemic stroke. A 1-˚C increase in temperature variability at 0-1 days (TV0-1) was associated with a 4.1% (1.9%-6.3%) increase of ischemic stroke onset. In a stratified analysis, men, people aged ≤ 65 years, and individuals with pre-existing hypertension, hyperlipidemia, hyperhomocysteinemia were more susceptible to temperature variability. Furthermore, the influence pattern of temperature variability on ischemic stroke was different in the cold season (November-April) and the warm season (May-October). Conclusion: Our findings suggested that short-term temperature variability exposure could increase the risk of ischemic stroke, which may provide new insights into the impact of climate change on health.